Agrobacterium tumefaciens-Mediated Plant Transformation: A Review - Azizi-Dargahlou, Shahnam; pouresmaeil, Mahin (Molecular biotechnology, 2024)
Agrobacterium tumefaciens -mediated plant transformation is the most dominant technique for the transformation of plants. It is used to transform monocotyledonous and dicotyledonous plants. A. tumefaciens apply for stable and transient transformation, random and targeted integration of foreign genes, as well as genome editing of plants. The Advantages of this method include cheapness, uncomplicated operation, high reproducibility, a low copy number of integrated transgenes, and the possibility of transferring larger DNA fragments. Engineered endonucleases such as CRISPR/Cas9 systems, TALENs, and ZFNs can be delivered with this method. Nowadays, Agrobacterium-mediated transformation is used for the Knock in, Knock down, and Knock out of genes. The transformation effectiveness of this method is not always desirable. Researchers applied various strategies to improve the effectiveness of this method. Here, a general overview of the characteristics and mechanism of gene transfer with Agrobacterium is presented. Advantages, updated data on the factors involved in optimizing this method, and other useful materials that lead to maximum exploitation as well as overcoming obstacles of this method are discussed. Moreover, the application of this method in the generation of genetically edited plants is stated. This review can help researchers to establish a rapid and highly effective Agrobacterium-mediated transformation protocol for any plant species.